BEHAVIOR OF CASTELLATED STEEL BEAM UNDER CYCLIC LOADS - Armin Aryadi (DINTEK, 2019)
Kastella steel profiles can be a practical solution in the construction , due to its characteristics which are quite favorable. The research aimed to determine (1) the failure shape of the castella beam, 2) the ability of castellan beam when used as the structural beam element resisting earthquake loads, and (3) the relationship of the behavioral parameters of the beam elements. The research used three types of tested beams made of the steel beams IWF 200 x 100 x 5.5 x 8; one pair of the normal beam (NB), one pair of the castella beam(CB), hexagonal-shape opening angle , the opening height of 0.6 H , the distance openings 9 cm , and the opening angle of 60. The testing used the portal system and loaded with the cyclicloads, in the form of displacement -controlled. The research results revealed that (1) indications failure of the tested beam due to yielding by flexure loads, (2) when compared to the flexure capacities of the NB beams, the increases of the flexure capacities of the CB were 84.36%, their partial displacement of ductility were 6,71, their full displacement of ductility were 6.86 beyond the limits of 5.2, the CB could be used as a structural element of the moment bearer frame system for the earthquake zone; (3) the flexural capacity was in proportion to the partial displacement and full displacement of ductility and inversely in proportion to the stiffness, the stiffness was inversely proportion to the partial displacement and full displacement of ductility. The relationship between these parameters is expressed in the model of equations.